Marine mammals in macro-ecosystems of Far Eastern seas and adjacent waters of the North Pacific - Vyacheslav P. Shuntov; Oleg A. Ivanov (Известия ТИНРО)
The article discusses the role of marine mammals in marine and oceanic ecosystems on the example by Far Eastern seas with adjacent waters of the North Pacific, one of the regions of the World Ocean distinguished for high biological and fish capacity along with a high abundance of cetaceans and pinnipeds. Based on extensive data, published mostly by Russian experts, the authors calculated the following quantities of annual consumption of fish and invertebrates by marine mammals in the three Far Eastern seas: 14.6-18.2 million t in the early 20th century, 12.3-15.1 million t in the late 1970s, 22.7-28.8 million t in the pre-harvesting period, and 24.0-24.7 million t in the early 21st century (27.0-29.5 million t, if 3-5 million t in ocean waters off the Kuril Islands and Kamchatka are taken into account). More than a half of this quantity is composed by zooplankton and zoobenthos, and then by fish and squids. In too time scales of food consumption by fishes and large-sized invertebrates are much higher than these estimates: in the layer 0-1,000 m, 516 million t was consumed in the 1980s-1990s, 389 million t in 1991-1995, and 461 million t in 1996-2005. In the years of high abundance, large-sized walleye pollock alone consumed nearly 40 million t of small-sized fish and squid. Based on the data of 35-year-long ecosystem studies by TINRO-Center, the following biomass estimates have been obtained for the biota of the Far Eastern Economic Zone of Russia: 1,000 million t of meso- and macroplankton, 500 million t of zoobenthos, 100 million t of nekton, 5 million t of benthic fish, and 2.43 million t of large-sized benthic invertebrates, which are not included in the benthos. Against the background of these estimates and comparing the volume of food consumption by marine mammals concluded that marine mammals in the Far Eastern Russian waters noticeable in food webs, but their role does not rise to a level sufficient for the regulation of the powerful sea and ocean makroekosistem.